2010
DOI: 10.2478/v10129-011-0001-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis for fiber quality traits in cotton

Abstract: Combining ability and heterosis for fiber quality traits in cotton Combining ability analysis and heterosis for cotton fiber quality traits were studied in a set of diallel crosses involving eight cotton (Gossypium sp.) genotypes. Randomized complete block design was used to test 56 F1 and 8 parents for fiber quality traits; length (Len), strength (Str), micronaire (Mic), uniformity (Unf), elongation (Elg), spinning consistency index (Sci) and short fiber index (Sfi). Analysis revealed significant gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
5
5
0
Order By: Relevance
“…Bolek et al 9 and Shah et al 10 were found similar results. The contradictory results were found by Hussain et al 11 and Esmail et al 12 (Table 2a-Table 2c) (Figure 1).…”
Section: Fiber Length (Mm)supporting
confidence: 53%
“…Bolek et al 9 and Shah et al 10 were found similar results. The contradictory results were found by Hussain et al 11 and Esmail et al 12 (Table 2a-Table 2c) (Figure 1).…”
Section: Fiber Length (Mm)supporting
confidence: 53%
“…Several studies have been reported on yield and yield attributing traits, but little work has been reported on the genetics and heterosis of fiber quality traits in cotton breeding. The work on heterosis has been reviewed for time to time on various quality and yield components in cotton by many workers (Karademir et al, 2009, Karademir and Gencer, 2010, Karademir et al, 2011, Bolek et al, 2011and Ashokkumar et al, 2013 and determined that cotton genotypes differ in fiber quality traits. Thus, the aim of heterosis analysis is to find out the best combination of parents for their prospects for future use in hybrid breeding programme.…”
Section: Introductionmentioning
confidence: 99%
“…Same results were obtained by Mehetre et al (2003). The opposite results were found by Ali et al (2008), Basal et al (2009) and Bolek et al (2011). Additive with partial dominant genes were found to be involved in the inheritance of fiber uniformity because regression line intercepts the Wr-axis above the point of origin (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Ali et al (2011) showed over dominance in number of monopodial and sympodial branches, boll weight and number of bolls per plant. Bolek et al (2011) studied heterosis and combining ability in fiber elongation, fiber uniformity, fiber fineness, fiber strength, fiber length, short fiber index and spinning consistency index. Additive type of gene action was found to be present in all characters.…”
Section: Introductionmentioning
confidence: 99%